(untitled) (Research, Society and Development, 2022)
The switched reluctance motor (SRM) has been considered a viable alternative to replace the classic electric motors in applications that require variable speed drives. This motor is robust, has a simple construction and the advantage of having a rotor that doesn’t need windings or permanent magnets to operate. In this paper, a four-phase 8/6 SRM is designed in order to replace a three-phase induction motor (IM), using the same frame available. In the design methodology adopted, the mechanical data of the three-phase IM frame are used as initial parameters for calculus of the SRM dimensions. The choice of the SRM’s pole arc angles is optimized by the finite elements analysis (FEA). Furthermore, the FEA simulations allows the visualization of the magnetic flux distribution in the SRM structure and the gathering of important data such as the inductance and flux linkage profiles, and also the designed motor’s torque. The largest relative error obtained for the magnetic flux density in the motor core was 1.69% and the SRM’s resulting torque was very close to the one required initially. The presented results validate the designed prototype and consolidate the design methodology used.